Early childhood education in rural areas: human emancipation or reproduction of social inequalities - Airan Celina Sepúlveda dos Santos Rocha de Abreu; Carmen Lúcia de Oliveira Cabral (Revista Brasileira de Educação do Campo)
The early childhood education, a stage within the school education system, presents many aspects to be problematized and implemented, especially when considering the implementation of this stage in the rural context. Among these aspects, the socio-cultural and historical context in which the child develops as a person and social being stands out, consisting of unique experiences, distinct from other spaces, demanding from the formal education planning a commitment to the local way of being. With this contextual characterization, the objective of this study is to analyze whether the educational principle of early childhood education in rural areas contributes/leads towards a socio-cultural emancipation education or towards confirming the inequalities between rural and urban areas. Drawing from a bibliographical study, this production has as its theoretical framework the contributions of Bauman (2008), Dubet (2001, 2004), Kramer (1982), Reay (2013), Sawaia (1999), Vincent, Lahire, and Thin (2001), among others, as well as legal documents relevant to Early Childhood Education in rural areas, texts analyzed according to the guidelines of critical discourse analysis technique. As results, we present the proposal of an early childhood education in rural areas with an emancipatory educational principle, supported by practices and discourses of inclusion, holistic human formation, and combating social inequalities.